STUDY IN THE EPIDEMIOLOGY OF SARCOCYSTOSIS SARCOCYSTIS CAMELI IN CAMELS IN AI-QADISIYAH PROVINCE - Al-Hamad, N. N. A.; Yacoub, A. Y.; Raishan, A. (The Iraqi Journal of Veterinary Medicine, 2021)
The aim of study was to investigate the prevalence of macroscopic and microscopic sarcocystosis of 312 camels slaughtered in Al-Qadisiyah province abattoirs. The developmental stages were studied in experimentally infected dogs with Sarcocystis cameli. For macroscopic sarcocystis naked eye examination was done while for microscopic type, the methods were employed (peptic muscular digestion, trichinoscopy, squeezing and histological examination) for the detection of infection in esophagus, heart, diaphragm and skeletal muscles. The percentage prevalence of macroscopic cysts were first recorded (0.64%) among the different organs examined. The rate of microscopic infection was (83.3%) in peptic digestion method followed by squeezing and trichinoscopy were 78.47 % and 58% respectively The highest rate of infection was recorded in the esophagus and the lowest in the heart. Histological examination revealed two different morphological cysts, the first one with thin wall and the other thick striated wall. The pre patent periods were 8-9 and 10-12day respectively, each infected dog-shed total about 32 * 10* sporocysts per gram of faeces. The peak of shedding reached 326*10* sarocystis per gram of faeces day12 post infection histological development stages of the parasite were detected in the small intestine mucosa of dog in days 6 and 12 post infection.